2014
DOI: 10.1590/brag.2014.008
|View full text |Cite
|
Sign up to set email alerts
|

Technological quality of common bean grains obtained in different growing seasons

Abstract: The traits that provide technological quality to common bean grains exhibit genetic and environmental variation and variation in the genotype x environment interaction. In this context, the aim of this study was to assess the effect of different periods of the growing season on the technological quality of common bean grains. The experiment was conducted with 25 bean genotypes (carioca [beige with brown stripes] and black commercial group) that are part of the Value for Cultivation and Use (Valor de Cultivo e … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
25
1
8

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 15 publications
3
25
1
8
Order By: Relevance
“…The CT values for the rainy season were lower than those of the dry and winter seasons, as expected, since the rainy season is considered most favorable for differentiating genotypes that are superior in cooking time (Perina et al, 2014). Nevertheless, in the literature, lower values are found for cooking time in the dry season (Perina et al, 2014), indicating that cooking time may also be related to the quality of the grain at the time of harvest.…”
Section: Resultssupporting
confidence: 67%
See 2 more Smart Citations
“…The CT values for the rainy season were lower than those of the dry and winter seasons, as expected, since the rainy season is considered most favorable for differentiating genotypes that are superior in cooking time (Perina et al, 2014). Nevertheless, in the literature, lower values are found for cooking time in the dry season (Perina et al, 2014), indicating that cooking time may also be related to the quality of the grain at the time of harvest.…”
Section: Resultssupporting
confidence: 67%
“…Among the genotypes evaluated, the CT ranged from 26'51" to 32'10" for the combination of the three crop seasons. This variation is due to the genetic differences present in the genotypes, environmental influence and genotype by environment interaction (Dalla Corte et al, 2003;Perina et al, 2014). The results for CT indicated that the Gen C2-1-6-1, Gen C2-3-1-1-2, BRS Cometa, LP 0403, IAC Imperador, and Gen P5-4-4-1 genotypes stood out in relation to the standard control for the carioca group, and the Gen Pr11-6-4-1-2 line stood out among the genotypes in the black group.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Carbonell et al (2003) found similar variation (34% of difference between the longest and the shortest time) from the evaluation in 12 environments, however, with lower averages for the elite lines, ranging from 18.0 to 24.1 minutes. Perina et al (2014) also found similar variability (28%), with the means of elite lines ranging from 26.2 to 33.5 minutes in 19 environments in the State of São Paulo. For two cultivars evaluated by these authors, BRS Estilo (32.3 minutes) and Pérola (31.3 minutes), also included in this study, the averages obtained for the cooking time were similar, 31.7 minutes for BRS Estilo and 32.5 minutes for Pérola.…”
Section: Resultssupporting
confidence: 57%
“…For two cultivars evaluated by these authors, BRS Estilo (32.3 minutes) and Pérola (31.3 minutes), also included in this study, the averages obtained for the cooking time were similar, 31.7 minutes for BRS Estilo and 32.5 minutes for Pérola. However, the average cooking time of BRS Cometa, also common to both studies, was 29.3 minutes in the evaluation of Perina et al (2014), and of 35.6 minutes, in this study, which were values with considerable difference, indicating differential interaction among the lines.…”
Section: Resultsmentioning
confidence: 37%